Pelatihan Penggunaan Peralatan Untuk Mendukung Peneliti Biologi dalam Penelitian Lapangan di Papua - Henderina J. Keiluhu; Euniche R.P.F. Ramandey; Heron Yando; Gison Morib; Yolanda Duwiri; Adhen Pramudianto; Mochtar Tanassy; Sarah Yuliana (Jurusan Biologi FMIPA Universitas Cenderawasih, 2026)
Papua, part of Indonesia, is an area that is very rich in biodiversity, both plant and animal biodiversity. To use it in the research field, it requires several tools to support field research. This training aims to introduce several research tools and applications commonly used in the field for youth in Yongsu Village as well as field officers from the Papua Province Natural Resources Conservation Centre. The training was held for two days, on 5 and 6 March 2026 at Yongsu Village, Ravenirara District, Jayapura Regency. This training was attended by 22 participants. The training method used is outreach about Papuan biodiversity as well as practice on how to use sweep nets, winkler apparatus, camera traps and the SMART patrol application. The results of this training showed that 77% strongly agreed with the training activities and 23% agreed. This shows that the participants really need training like this to improve the quality of their skills in using tools that support their daily work as researchers and research assistants in the field when conducting research.